College Algebra 7th Edition

Published by Brooks Cole
ISBN 10: 1305115546
ISBN 13: 978-1-30511-554-5

Chapter 2, Functions - Section 2.8 - One-to-One Functions and their Inverses - 2.8 Exercises: 68

Answer

$f^{-1}(x) = (x - 2)^{2} - 3, x\geq2$

Work Step by Step

$f(x) = 2 + \sqrt {3 + x}$ $y= 2 + \sqrt {3 + x}$ $y - 2 =\sqrt {3 + x}$ $(y - 2)^{2} = (\sqrt {3 + x})^{2}$ $(y - 2)^{2} = 3 + x$ $x = (y - 2)^{2} - 3$ $f^{-1}(x) = (x - 2)^{2} - 3, x\geq2$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.